Organochlorine pesticides in Piracicaba river basin (São Paulo/Brazil): a survey of sediment, bivalve and fish - Daniela Mariano Lopes da Silva; Plínio Barbosa de Camargo; Luiz Antonio Martinelli; Fernando Mauro Lanças; Jair S. S. Pinto; Wagner E. Paiva Avelar (Química Nova, 2008)
The main objective of this paper was to evaluate the level of occurrence of the organochlorine compounds in samples of sediments, bivalves and two fish species collected in the Piracicaba River basin (São Paulo, Brazil). The isomers alpha and gamma of HCH and Heptachlor were most frequently detected in samples of sediments and specimens of bivalve and fish. Therefore, although the levels of these compounds found were not critically high, they are still found in the environment. This fact suggests that they are still being used, despite the fact that the use of these compounds was outlawed more than twenty years ago.